2006
DOI: 10.2355/isijinternational.46.1137
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow in a Combined Top and Bottom Blown Reactor

Abstract: Physical modeling was done to study the flow field in a cylindrical bath agitated by bottom purging, top lance blowing and a combination of both injection types. A particle image velocimetry (PIV) system has been used to capture the velocity field of all three cases mentioned above. Special attention was paid to the recirculation loop. Top blowing creates a re-circulation loop in a relatively small volume close to the surface, compared to bottom-and combined-blowing. Increasing bottom flow rate moves the cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The high mixing efficiency in the converter is largely attributed to stirring effects of the bottom injected gas. Therefore, the effects of various bottom nozzles conditions, [16][17][18][19]24,80,83) gas flow rates and gas supply schemes, 21,22,25,48,140) and combination schemed of top gas and bottom gas 20,26,27,30,78,79,119,141) are studied to optimize the mixing effects in the converter. The velocity distribution inside a 335-ton converter bath as well as the velocity and bubble size distribution in a six plugs 190-ton bottom blown converter with standard bottom stirring are presented in Fig.…”
Section: Stirring and Mixing Behaviormentioning
confidence: 99%
“…The high mixing efficiency in the converter is largely attributed to stirring effects of the bottom injected gas. Therefore, the effects of various bottom nozzles conditions, [16][17][18][19]24,80,83) gas flow rates and gas supply schemes, 21,22,25,48,140) and combination schemed of top gas and bottom gas 20,26,27,30,78,79,119,141) are studied to optimize the mixing effects in the converter. The velocity distribution inside a 335-ton converter bath as well as the velocity and bubble size distribution in a six plugs 190-ton bottom blown converter with standard bottom stirring are presented in Fig.…”
Section: Stirring and Mixing Behaviormentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Ersson et al 1,2) employed both water-model experiments and mathematical modeling to study the effects of the top-blown jet on the steel bath in a LD converter. Also, Hirata et al 3) showed the stirring effect induced by top and side blown oxygen and bottom blown nitrogen converter.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several experimental reports on the subject for instance [1][2][3][4][5][6][7] and also some numerical or Computational Fluid Dynamics (CFD) reports. [8][9][10][11][12][13] Szekely and Asai 8) presented a computational model of a jet impinging onto a liquid surface. Ngyen and Evans investigated the effect the nozzle-to-pool diameter ratio had on the deformation of the liquid surface caused by an impinging jet, using a computational model.…”
Section: Introductionmentioning
confidence: 99%
“…13) Here an extension to this model is presented which includes reactions i.e. a gas/liquid/slag Volume of Fluid (VOF) 17) multiphase model, for a top blown system.…”
Section: Introductionmentioning
confidence: 99%